Análise de pavimentos de edifícios em concreto préfabricado considerando o efeito diafragma - Raymundo, Henrique (2012)
One of the main differences in the structures composed of prefabricated elements of the conventional structures (cast in situ) refers to the way of how structural elements are connected together. The operation of such links is essential to perform an accurate analysis of stability and removed from these buildings. A place where the connection is very important in verifying the structural behavior is among the cellular elements of the slab. In a conventional structure, usually made of solid slabs for floors, it is observed that the behavior of slabs have a great influence on the distribution of efforts arising from actions horizontal resistance between the porch and, consequently, the stability of the same. This phenomenon, defined as a rigid diaphragm, can also be found in precast buildings, with floors composed of hollow core slabs. In order to verify the necessity of including some details of connection between the slab elements (joints between the slabs and among other things) will be proposed in this paper the analysis of five structures with different characteristics, considering the different possibilities of bracing and disposal of prefabricated slabs in the floor. Consideration will be given the difference in the distribution efforts of the pavements, considering the application of shear walls and gateways, as well as the provision of slabs parallel and perpendicular to side action. The interference of the cover structure will also be analyzed in a number of examples. From a modeling specific to the floors of these buildings and different situations with different levels of horizontal actions, one can determine the stresses at specific points of the same, thus indicating the types of reinforcements to be willing to actually floors act as a diaphragm. Finally, we intend to discuss the organization of prefabricated elements interfere in the distribution of efforts on the pavement (joints between the slab elements), based on different amounts of reinforcing bars of each type of pavement structure will require.